Observational astronomy techniques and instrumentation - Sutton, Edmund Charles (Cambridge University Press, 2012)
"Astronomy is fundamentally an observational science and as such it is important for astronomers and astrophysicists to understand how their data are collected and analyzed. This book is a comprehensive review of current observational techniques and instruments. Featuring instruments such as Spitzer, Herschel, Fermi, ALMA, Super-Kamiokande, SNO, IceCube, the Auger Observatory, LIGO and LISA, the book discusses the capabilities and limitations of different types of instruments. It explores the sources and types of noise and provides statistical tools necessary for interpreting observational data. Due to the increasingly important role of statistical analysis, the techniques of Bayesian analysis are discussed, along with sampling techniques and model comparison. With topics ranging from fundamental subjects such as optics, photometry and spectroscopy, to neutrinos, cosmic rays and gravitational waves, this book is essential for graduate students in astronomy and physics"--